Momente - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2010)
MOMENTE / MOMENTS for soprano, 4 choir groups and 13 instrumentalistsEurope Version 1972 (CD 7 A-B) and Donaueschingen Version 1965 (CD 7 C)(conductor: K. Stockhausen) 3 CDs with 4-colour text booklet (80 pages, German-English)and separate book with complete sung texts (32 x 27 cm, 36 pages, colour print)